THE INFLUENCE OF ORGANIZATIONAL CULTURE, INTERNAL COMMUNICATION, AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT THE TRANSPORTATION DEPARTMENT OF BANDAR LAMPUNG CITY - Saskia Indah Prameswari; Iskandar Ali Alam (International Journal of Economics, Business and Accounting Research (IJEBAR), 2026)
Employee performance is a key factor in the effectiveness of public organizations, especially in service-oriented agencies such as the Transportation Agency of Bandar Lampung City. Organizational culture, internal communication, and work discipline are suspected to play a strategic role in shaping work behavior and employee productivity. This study aims to assess the influence of organizational culture, internal communication, and work discipline on employee performance, both individually and collectively. A survey approach is employed in conjunction with an explanatory quantitative research method. Data were subjected to classical assumption tests, reliability tests, validity tests, and multiple linear regression analysis. (1) Organizational culture positively and significantly impacts employee performance; (2) Internal communication positively and significantly affects employee performance; (3) Work discipline positively and significantly influences employee performance; and (4) Organizational culture, internal communication, and work discipline collectively have a significant effect on employee performance. Work discipline was proven to be the most dominant variable affecting performance.